Urban Spatial Naturalness Degree in the Planning of Ultra-High-Density Cities: The Case of Urban Green Open Spaces in Macau - Jitai Li; Fan Lin; Hongcan Cui; Shuai Yang; Yile Chen (Buildings)
This study deeply examines the livable environment in high-density cities like Macau, focusing on urban green spaces. The study introduces the “urban spatial naturalness degree” indicator, exploring its application with urban population growth and green space expansion. The research utilizes the planning indicator of “urban spatial naturalness degree”, and then explores the application paradigm of matching increments between urban population growth and green open space and a bottom-line planning indicator suitable for Macau. Among them, the “USND” indicator is defined as “the visual perception rate of blue and green natural elements in the three-dimensional space of urban land”, which is specifically expressed as “the average function of the occupation rate of urban green open space and the visibility rate of blue–green space of main street scenes”. Based on this, this paper estimates the incremental planning indicators of green open space in Macau and various urban areas during the implementation of the Master Plan of Macau (2020–2040). The results show the following: (1) The study found that the land increment in green open space in Macau basically matches the potential of reserve resources. (2) For Class I and Class II urban areas in Macau, the USND value is estimated to be 42.96% and 32.62% in 2040, respectively. These values are expected to reach the international excellent level. (3) For Class III and Class IV urban areas, the USND values could reach 20.14% and 15.14%, respectively, which are considered to be at the international middle level in 2040.